Case report: complete response and long-term survival on third-line immunotherapy in patient with pleural mesothelioma - Jurić Čuljak, Željka; Tomić, Snježana; Šitum, Kristina; Boraska Jelavić, Tihana (Frontiers in Oncology, 2024)
IntroductionPleural mesothelioma (PM) is a rare neoplasm with median survival time range from 8 to 14 months from diagnosis, and the 5-year survival rate less than 10%, indicating a poor prognosis. The standard treatment for unresectable PM for a long time has been polychemotherapy with pemetrexed and cisplatin for fit patients. Currently, the combination of the anti PD-1 inhibitor nivolumab and the anti-CTLA4 inhibitor ipilimumab has been recognized as the best possible frontline therapy (especially in the sarcomatoid or biphasic type) due to improved outcomes compared to the standard chemotherapy combination. There are still no established predictive biomarkers for any type of systemic therapy in this disease.Case presentationPatient who presented with cough and dyspnea has been diagnosed with advanced epithelioid type PM in May 2016. He was treated with three lines of therapy, including an antiangiogenic agent and immunotherapy with pembrolizumab in the third line. Immunotherapy with the PD-1 inhibitor pembrolizumab achieved a complete and prolonged response that transferred to long- term survival. Seven years from diagnosis, the patient is still alive. Histological findings showed an unusually immune-inflamed tumor microenvironment possibly leading to excellent response on immunotherapy.ConclusionsThe course of the disease in our patient points out that we need better predictive biomarkers to direct the treatment algorithm, as some of the patients, although chemorefractory to the best chemotherapy option, can sustain great benefit of second-line chemotherapy in combination with antiangiogenic agent, and especially immunotherapy, even in late lines of therapy.